2004
DOI: 10.1063/1.1812599
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the metal-insulator transition temperature in thin La0.7Sr0.3MnO3 films

Abstract: In this paper, we illustrate an approach to discriminate between\ud epitaxial strain and other factors responsible for the decrease of the\ud metal-insulator transition temperature (T-P) in thin La0.7Sr0.3MnO3\ud films grown by pulsed laser deposition. Using this approach, we have\ud estimated the effect of the biaxial strain on T-P. Ultrathin films,\ud independent of epitaxial strain, do not show any metal-insulator\ud transition over the full temperature range. This finding confirms the\ud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
66
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 18 publications
12
66
0
Order By: Relevance
“…The ob- Similar measurements were performed on our films; they confirm the presence of a critical thickness of this order of magnitude. 4 Figure 2(b) shows the thickness dependence of the applied rf field h required to optimally excite the f DE NMR resonance. The reduction of h with increasing film thickness indicates an increase of the experimental enhancement factor η = h/h 0 , as given by Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ob- Similar measurements were performed on our films; they confirm the presence of a critical thickness of this order of magnitude. 4 Figure 2(b) shows the thickness dependence of the applied rf field h required to optimally excite the f DE NMR resonance. The reduction of h with increasing film thickness indicates an increase of the experimental enhancement factor η = h/h 0 , as given by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Deposition conditions, structural characterization and transport properties have been described elsewhere. 4 It should be mentioned here that the annealing duration for optimal oxygen content was found to vary with film thickness: two hours for thicker films and half an hour and less for thinner films.…”
Section: Materials and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16] In this work, we investigate the magnetotransport properties of fully commensurate epitaxial La 0.7 Sr 0.3 MnO 3 thin films grown by reactive molecular-beam epitaxy. Our films span a biaxial strain range from Ϫ2.3% to +3.2%, and we find excellent agreement between the measured Curie temperatures and the model of Millis et al 5 The films were grown on nine commercially available perovskite substrates: ͑100͒ p LaAlO 3 , ͑001͒ LaSrGaO 4 , ͑110͒ NdGaO 3 , ͑100͒ ͑LaAlO 3 ͒ 0.3 -͑SrAl 0.5 Ta 0.5 O 3 ͒ 0.7 ͑LSAT͒, ͑100͒ SrTiO 3 , ͑110͒ DyScO 3 , ͑110͒ GdScO 3 , ͑110͒ SmScO 3 , and ͑110͒ NdScO 3 , where the subscript p indicates pseudocubic indices.…”
mentioning
confidence: 99%
“…25 Thiele et al have shown that voltagecontrolled epitaxial strain in LSMO is possible when exploiting the inverse piezoelectric effect of Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (001) (PMN-PT) substrates. 26 They report on voltage-controlled changes of the Curie temperature in a LSMO film of 20 nm thickness between 278 K and 297 K. Fig.…”
mentioning
confidence: 99%